A survey on communication components for IoT-based technologies in smart homes - Zaidan A.A.; Zaidan B.B.; Qahtan M.Y.; Albahri O.S.; Albahri A.S.; Alaa M.; Jumaah F.M.; Talal M.; Tan K.L.; Shir W.L.; Lim C.K. (Springer Science and Business Media, LLC, 2023)
Automation; Home networks; Intelligent buildings; Personal communication systems; Quality of service; Surveys; Analytical studies; Communication components; Comparative studies; Development and utilizations; Home automation systems; Internet of Things (IOT); Smart Home Technology; Telecommunication standards; Internet of things